2018
DOI: 10.18823/asiatefl.2018.15.4.13.1083
|View full text |Cite
|
Sign up to set email alerts
|

English as a Medium of Instruction : A Case Study at a Gifted High School in Vietnam

Abstract: This paper aims to examine the perceptions of teachers and students at a gifted high school in Central Vietnam about teaching science subjects such as Maths, Chemistry, Physics, and Biology through English. Using questionnaires, in-depth interviews, and class observations as research instruments, this study also explores the challenges the administrators, teachers, and students are facing in adopting English as a medium of instruction (EMI). The findings revealed that leaders, teachers, and students appreciate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Tuy nhiên, qua hơn một thập kỷ thực hiện, giáo dục CLIL vẫn còn kém phát triển và tồn tại những vấn đề lớn liên quan đến hoàn cảnh xã hội và tài chính, mức độ sẵn sàng của học sinh và đặc biệt là chất lượng giáo viên. Tại Việt Nam, việc triển khai CLIL gặp rất nhiều khó khăn do tình trạng thiếu giáo viên CLIL đạt chuẩn (Le, 2012;Nguyen & Ngo, 2018;Nhan, 2013;To, 2010), thiếu các chương trình phát triển chuyên môn cho giáo viên CLIL Nguyen và cộng sự, 2024) cũng như các rào cản bên ngoài (Thái và cộng sự, 2020). Điều này một lần nữa khẳng định nhu cầu đào tạo, phát triển năng lực ngôn ngữ và năng lực sư phạm của giáo viên CLIL.…”
Section: đặT Vấn đềunclassified
“…Tuy nhiên, qua hơn một thập kỷ thực hiện, giáo dục CLIL vẫn còn kém phát triển và tồn tại những vấn đề lớn liên quan đến hoàn cảnh xã hội và tài chính, mức độ sẵn sàng của học sinh và đặc biệt là chất lượng giáo viên. Tại Việt Nam, việc triển khai CLIL gặp rất nhiều khó khăn do tình trạng thiếu giáo viên CLIL đạt chuẩn (Le, 2012;Nguyen & Ngo, 2018;Nhan, 2013;To, 2010), thiếu các chương trình phát triển chuyên môn cho giáo viên CLIL Nguyen và cộng sự, 2024) cũng như các rào cản bên ngoài (Thái và cộng sự, 2020). Điều này một lần nữa khẳng định nhu cầu đào tạo, phát triển năng lực ngôn ngữ và năng lực sư phạm của giáo viên CLIL.…”
Section: đặT Vấn đềunclassified
“…However, gifted students' perceptions have not received much attention from researchers. From the literature review, only a few of such studies can be found (Vu, 2011;Vu & Vu, 2012;Nguyen, Jin & Gross, 2013;Nguyen & Ngo, 2018). Vu (2011) examined gifted students' profiles and their perceptions towards a gifted program.…”
Section: Relevant Research On Elf and Gifted Studentsmentioning
confidence: 99%
“…Nguyen, Jin, and Gross (2013) investigated the Confucian values in Vietnamese gifted adolescents and their regular peers. Nguyen and Ngo (2018) conducted research on teachers' and students' perceptions towards English as a medium of instruction at a gifted high school in Central Vietnam. Apparently, a study on gifted students' perceptions of ELF would be a great contribution to the gap in the literature and the practical implementation of English language teaching at Vietnamese gifted high schools.…”
Section: Relevant Research On Elf and Gifted Studentsmentioning
confidence: 99%
“…This will enable them to be more confident in communication, further their chance to study and work in an integrated and multi-cultural environment with a variety of languages. The goals also make using foreign languages as an advantage for Vietnamese people, serving the cause of industrialization and modernization for the country (Nguyen & Ngo, 2018). According to Nguyen and Ngo (2018), the decision is the basis for comprehensively reforming basic education, improving the structure of the national education system; consolidating the teacher training system, innovating comprehensive contents and training methods, implementing preferential policies for the physical and spiritual motivation for teachers and education managers; innovating content, teaching methods, examinations; investigating and evaluating the quality of education; expanding and improving the efficiency of international cooperation in education, developing and application of educational methods of some advanced education systems.…”
Section: National Foreign Languages Project 2020 and Textbooks Innovamentioning
confidence: 99%